Sleep, Workload and Boredom: Subject Matter Expert Insights. (September 2016) - Volante, W. G.; Merz, M.; Stowers, K.; Hancock, P. A.
As human spaceflight evolves toward long duration space missions (LDSM), it becomes increasingly important to design mission specifications and crew schedules that account for fluctuations in cognitive and psychomotor workload. Such schedules should optimize both sleep and workload to maintain high levels of mission performance. Effective sleep and workload scheduling tools are thus imperative for success, as they facilitate enhanced sleep quality and adjustable workload profiles for superior task performance. Here we examine issues related to sleep in space by taking two approaches: (1) completion of a systematic literature analysis, and (2) completion of interviews with Subject Matter Experts. Both of these approaches are summarized, with key findings and implications discussed.